Analisis Pendapatan dan Pembiayaan pada Rencana Kegiatan Anggaran Sekolah - Inggit Hascaryani; M. Nurudin; Giyoto Giyoto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to compare the amount, source of income, and expenditure allocation in the school budget plan (RKAS) in the last three years, namely 2018, 2019 and 2020. This study uses the content analysis method. The data sources came from the 2018, 2019 and 2020 RKAS documents. Data analysis used quantitative with percentages and descriptive qualitative. The results show that the amount of revenue in 2018 is higher than 2019 and 2020 is higher than 2018. Source of revenue for 2018 comes from central and regional BOS, while in 2019 and 2020 only central BOS. The expenditure allocation in 2018 was the highest in financing standards, in 2019 the highest was in management standards and in 2020 the highest was in financing standards.